KAJIAN SENYAWA HEXOSE DAN MALIC ACID SEBAGAI INHIBITOR PAPAIN LIKE PROTEASE (PLPro) CORONA VIRUS - Yohanes Bare; Frederiksen Novenrius Sini Timba; Sukarman Hadi Jaya Putra; M A Yohanita Nirmalasari; Dewi Ratih Tirto Sari; Maximus M Taek (JURNAL BIOSENSE, 2022)
Papain-like protease is a SARSCOV-2 protease that functions for ubiquitination in host cells. Caffeine compounds have been widely reported to have antioxidant, anti-inflammatory, antidiabetic, and antiobesity activities. However, hexose and malic acid compounds in coffee rind as potential inhibitors of the papain-like protease SARSCOV2 have not been reported. This study investigated the potential of malic acid and hexose compounds as PLPro inhibitor agents in inhibiting SARSCOV2 ubiquitination. In silico studies were used to identify the potential of the two compounds by interacting hexose and malic acid compounds with papain-like protease (PLPro) proteins with the Molegro virtual Docker 5 program. Next, the ligand-protein complex visualization was done with discovery studio version 5.0. hexose and malic acid compounds showed interactions with papain-like protease proteins on several active site residues. The interactions showed inhibition of ubiquitination and stimulation of interferon in host cells. The two compound complexes – PLPro protein showed hydrophobic interactions, hydrogen bonds, and van der Waals forces, which contributed to the formation of bond energy and strong bonds between compounds and proteins. In this study, it was concluded that hexose and malic acid compounds have the potential to act as inhibitors of papain-like protease (PLPro) protein.